The Impact of Influencer Marketing on Brand Perception and Consumer Purchase Intentions: A Social Influence Theory Perspective - Saritha, M.; Anupama, P.; Jalaja, S.; Thakur, Reena (International Journal of Psychosocial Rehabilitation, 2019)
This research explores the impact of influencer marketing on brand perception and consumer purchase intentions through the lens of Social Influence Theory. In the digital age, influencer marketing has become a crucial strategy for brands aiming to shape consumer attitudes and drive purchasing decisions. Social Influence Theory provides a framework for understanding how influencers, as social agents, affect consumer behavior by leveraging both normative and informational influence. This study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews, to assess how influencer endorsements alter brand perception and influence purchase intentions. The findings indicate that influencers significantly impact brand perception by enhancing credibility and relatability, which in turn affects consumer purchase intentions. The research contributes to the understanding of the mechanisms through which influencer marketing operates and offers practical insights for brands seeking to optimize their marketing strategies in alignment with Social Influence Theory.